Making The Invisible Visible: A Phenomenological Exploration Of Teacher Experiences with Digital Simulations - Gemcer Selda; Princes Joy S Muyo; Princess Ann P Pelaez (Advanced Qualitative Research, 2026)
This study explores the personal experiences of elementary teachers using digital simulations to teach difficult science topics. Using a phenomenological approach, the research looks at how eight (8) science teachers make sense of their roles when using these digital tools. Through deep interviews, the study found that simulations are more than just tools; they change how teachers think about and plan their lessons. The findings show that simulations help teachers turn abstract ideas into "real" experiences for students, which changes the way teachers decide to explain complex topics. While teachers faced frustrations like poor internet or a lack of training, they learned to adapt their teaching styles to overcome these hurdles. This study goes beyond just listing the pros and cons; it explains how teachers’ mindsets shift when they bring technology into the science classroom, offering new insights into the deep connection between a teacher’s choices and the tools they use.